Experimental techniques for the study of the degradation of pla and its blends - Chamorro López, Cindhy Jazmín (2021)
Poly (lactic acid) (PLA) can decompose under environmental conditions through chain scission, forming non-toxic subproducts. The influence of abiotic environmental factors on the destruction of biodegradable polymers is important to evaluate and predict the period of their full degradation in the environment. This review shows recent research involving biodegradation in abiotic environments and studies the influence of moisture, temperature, ultraviolet (UV) radiation, sunlight, and pH, as well as the experimental techniques employed to analyze the degradation of PLA and its blends such as Differential Scanning Calorimetry (DSC), Thermogravimetric analysis (TGA), X-Ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR), Nuclear Magnetic Resonance (NMR), Scanning electron microscopy (SEM) and Mechanical tests. These changes can be observed through the decrease in the molar mass of PLA, which can be monitored by Gel Permeation Chromatography (GPC) and 1H NMR. On the other hand, thermal transitions, typically studied by DSC, exhibit modifications during degradation; the glass transition, the crystallization and melting processes show different behaviors, depending on the type of degradation and the components present in the blends. The XRD technique provides relevant information on crystallization that can be used to complement DSC results. Meanwhile, the thermal stability of PLA is affected as a consequence of abiotic degradation, showing a decrease in thermal decomposition temperatures in most cases, as reported in the TGA tests. Chemical changes that occur during degradation can be observed by FTIR and NMR. Degradation also affects the morphology of PLA and its blends, both the surface of the samples, showing evidence of erosion, as in the interaction of the phases. Finally, the mechanical tests proved to be very sensitive to the changes caused by the degradation, being able to show the degradation much earlier than in the other techniques reviewed. The compilation of these results demonstrate that the combination of all characterization techniques is a useful strategy for monitoring the degradation process and assessing changes on PLA structure induced by different types of abiotic degradation.